AN ANALYSIS OF STUDENTS' DIFFICULTIES IN WRITING IMPERATIVE SENTENCE ON PROCEDURE TEXT AT SECOND GRADE KULINER 7 IN SMKN 9 PADANG - Lidya Nurhuda; Rahma Dania; Suparmi (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2023)
This research aims (1) to find out the difficulties students find in writing cimperative sentences in procedural texts, (2) to find out the factors that cause students to have difficulty writing imperativ sentences in second grade Culinary 7 procedure texts at SMKN 9 Padang. This research is a qualitative research. The data collection techniques are observation, written tests, and interviews. The research subjects were 27 second grade students of Culinary 7 at SMKN 9 Padang. The indicators of difficulty studied are social function, structure and linguistic features. From the data obtained, as many as 10% of students experienced difficulties with the social function indicators, 40% of students experienced difficulties with the structure indicators, and another 50% experienced difficulties with the linguistic feature indicators. Factors that influence students' difficulties in writing imperative sentences in procedural texts are students' lack of proficiency in English and ineffective learning strategy.